Nuclear and genome organization of Trypanosoma brucei. - Ersfeld, K; Melville, SE; Gull, K (1999)
In this article, Klaus Ersfeld, Sara Melville and Keith Gull review current understanding of the structural organization of the nucleus of Trypanosoma brucei, and summarize recent data pertinent to the organization of its genome. Until recently, the cell biology of the trypanosome nucleus and issues of DNA organization and gene expression have often been treated as separate themes. However, recent work emphasizes the need for a more holistic approach to understanding these aspects of the biology of this parasite.